Radical nephrectomy for a giant chromophobe renal cell carcinoma diagnosed > 17 years previously: a case report and literature review - Lan, Jianhua; Lan, Dong; Yuan, Wenqiang; Ying, Qiao; He, Jiahong; Gu, Yonglin (Frontiers in Oncology, 2024)
Early diagnosis of renal cell carcinoma relies on imaging tests such as ultrasound, computed tomography, or magnetic resonance imaging. Since surgery is associated with a favorable prognosis, the standard treatment for clinically limited renal cell carcinoma remains surgical resection. Among asymptomatic patients with localized renal cell carcinoma, a small number refuse surgical treatment and survive. We report a case involving a 59-year-old female who underwent a difficult radical nephrectomy 17 years after being diagnosed with malignant tumors due to primary renal cell carcinoma.